Transient Analysis of Thin-Wire Antennas over Debye Media - Pantoja, Mario F.; Bretones, Amelia R.; García, Salvador G.; Martín, Rafael G.; Travassos, X. Lucas (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents a numerical procedure to calculate the time-domain response of thin-wire antennas over Debye media. The method is based in an expansion of the electricfield integral-equation in the time-domain (EFIETD), which accounts for the Debye media by using a reflection-coefficient approach. Resulting extended integral equation is subsequently solved by the method of moments. Numerical examples including Debye soils show not only the accuracy of the method but also a higher computational efficiency in comparison with other hybrid numerical techniques.